Supporting sustainable urban transformation: a feasibility framework for smart city projects - Esteban-Narro, Rafael; Lo-Iacono-Ferreira, Vanesa G.; Torregrosa-López, Juan Ignacio (Frontiers in Sustainable Cities, 2025)
Smart city initiatives are increasingly promoted as strategies to foster urban sustainability. However, their actual impact largely depends on the feasibility and success of individual projects through which these strategies are implemented. Despite this relevance, feasibility analyses remain scarce in the scientific literature, particularly for small and medium-sized cities, where limited resources and high opportunity costs demand careful decision-making. This study addresses this gap by proposing a comprehensive and practical framework specifically designed to evaluate the feasibility of smart city projects in resource-constrained contexts. The framework is developed through a systematic literature review and a multi-stage analysis, resulting in a structured set of 38 indicators grouped into five core subject areas: spatial-population impact, social perception, technical readiness, institutional capacity, and economic-financial viability. It comprises a descriptive component, which gathers essential project data, and an evaluative component, which applies multicriteria decision-making techniques (Analytic Hierarchy Process) to generate feasibility scores for each thematic dimension. The framework was applied to a case study of implemented projects in a small city, offering exploratory findings on its capacity to anticipate outcomes and laying the groundwork for broader empirical validation across diverse urban contexts. Spearman correlation results revealed the decisive role of social acceptance and institutional support, while showing that technical readiness, though necessary, is not sufficient on its own. Designed as a decision-support tool for policymakers and urban planners, the framework fosters more transparent and inclusive governance and aligns with international agendas such as the UN Sustainable Development Goal 11.